Methodologically Historicizing Social Studies Education: Curricular Filtering and Historical Thinking as Social Studies Thinking - Smith, Bryan (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
This article explores the implementation of what the Ontario Ministry of Education (OME) calls “social studies thinking concepts” in its current social studies, history, and geography curriculum. As a six-part framework largely influenced by historical thinking, I argue that the OME, in essence, creates a context wherein historical thinking, beyond simply influencing social studies thinking, comes to largely conflate with social studies thinking through what I call a curricular filter, a process of including incompatible or incongruous ideas through more amenable language. I suggest that this is incongruent with the OME’s positioning of social studies as an integrated field and effectively denies social studies of its inherent interdisciplinary nature by privileging historically informed methods of inquiry.